Public Acceptance of Mobile Civic Service in Indonesia Using a Unified Model of E-Government Acceptance - Nugroho, Rino Ardhian; Imania, Annisaa Nurlaila; Rahmawati, Annisa Alya (KnE Social Sciences, 2022)
The Presidential Instruction No. 3 of 2003 on National Policy and Strategy for e-Government Development, has posed its own set of challenges, particularly for local governments in terms of providing responsive, effective, and efficient public services that lead to electronic public service innovations. The application of ”Dukcapil Dalam Genggaman” is a type of public service innovation based on the electronic output of Surakarta City’s Population Office and Civil Registry. The goal of this study was to use the Unified Model of Electronic Government Adoption (UMEGA) to assess the elements of public acceptability in the application ”Dukcapil Dalam Genggaman,” with data from 100 respondents. This was a quantitative study which used associative research and surveying approaches. Data were analyzed using Partial Least Squares (PLS). The results showed that there were five aspects or variables that influenced the acceptability of the application ”Dukcapil Dalam Genggaman” by the user community, including expectations of effort, facilitating conditions, perceived risk, attitude, and behavioral intentions. The public acceptability of users of “Dukcapil Dalam Genggaman” was unaffected by performance expectancy and social influence. Keywords: Dukcapil Dalam Genggaman, e-government, UMEGA, public acceptance